War made new weapons, warriors and the making of the modern world - Boot, Max 1968- (Gotham Books, 2006)
"A history that ranges from the defeat of the Spanish Armada to the War on Terrorism, War Made New is a provocative new vision of the rise of the modern world through the lens of warfare. Max Boot explores how innovations in weaponry and tactics have not only transformed how wars are fought and won but also guided the course of human events, from the formation of the first modern states, to the collapse of the Soviet Union, to the coming of al Qaeda." "Boot argues that the past five centuries of history have been marked not by gradual change in how we fight but instead by four revolutions in military technology - and that the nations who have successfully mastered these revolutions have gained the power to redraw the map of the world."--BOOK JACKET.